Simulation of spline based NC- manufacturing of plastic optical components - Nik Anwar, Nik Syahrim; Mohd Rusdy , Yaacob; Md Sani, Zamani (2011)
The paper discusses about the precision of manufacturing aspheric surfaces based on spline interpolation method. Splines are used in defining the tool path of an NC-machine in order to improve the precision. A spline based postprocessor with integrated testing function is created with Matlab. The algorithm, optimization, and the results of the postprocessor will be discussed.